2018
DOI: 10.1177/1179572718790937
|View full text |Cite
|
Sign up to set email alerts
|

A Multidisciplinary Preoperative Teaching Session for Women Awaiting Breast Cancer Surgery: A Quality Improvement Initiative

Abstract: Most of the breast cancer diagnoses are recommended for breast surgery. Unfortunately, many patients report preoperative anxiety, which can affect postoperative recovery. Preoperative teaching sessions have been shown to reduce anxiety and improve recovery for the patients with breast cancer. To better support the patients at our cancer center, a multidisciplinary preoperative teaching session was developed and delivered as a quality improvement initiative. MeThodS: Participants scheduled for breast surgery we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…This finding may also illuminate which patients may need additional support before their breast cancer surgery, especially since breast cancer patients reporting poor health symptoms before surgery may be at risk for reporting worse postoperative health outcomes [35]. Some studies have shown that increasing education and knowledge in distressed breast cancer patients before their surgery can significantly decrease their anxiety levels before their surgery [36]. This study's observation between younger age and worse mental health could be observed for a variety of reasons.…”
Section: Discussionmentioning
confidence: 64%
“…This finding may also illuminate which patients may need additional support before their breast cancer surgery, especially since breast cancer patients reporting poor health symptoms before surgery may be at risk for reporting worse postoperative health outcomes [35]. Some studies have shown that increasing education and knowledge in distressed breast cancer patients before their surgery can significantly decrease their anxiety levels before their surgery [36]. This study's observation between younger age and worse mental health could be observed for a variety of reasons.…”
Section: Discussionmentioning
confidence: 64%
“…These changes were statistically significant (p < 0.01), as indicated by Wilcoxon Signed-ranks tests. Similarly, following a group information session by the program physiotherapist, self-reported knowledge on bca rehabilitation-related content increased significantly (Ibrahim et al, 2018).…”
Section: Acceptabilitymentioning
confidence: 94%
“…Il s'agit là de changements statistiquement significatifs (p < .01), comme en témoignent les tests de rangs signés de Wilcoxon. De même, après une séance d'information de groupe organisée par la physiothérapeute du programme, les connaissances des femmes sur la réadaptation et le cancer du sein ont augmenté de manière appréciable (Ibrahim et al, 2018).…”
Section: Acceptabilitéunclassified